Asymmetric rotations and dimerization driven by normal to modulated phase transition in 4‐biphenylcarboxy coupled l‐phenylalaninate. Issue 2 (1st March 2023) - Dey, Somnath; Sasmal, Supriya; Mondal, Saikat; Kumar, Santosh; Chowdhury, Rituparno; Sarkar, Debashrita; Malla Reddy, C.; Peters, Lars; Roth, Georg; Haldar, Debasish
Abstract : Crystals of a coupled molecule of 4‐biphenylcarboxy‐(l )‐phenylalaninate undergo normal to commensurately modulated phase transition at T c ∼ 124 K that is characterized by torsional modulation typical of modulated structures and superstructures of polyphenyls yet unusual owing to asymmetric and unequal rotations governed by intramolecular and intermolecular constraints. The transition is presumably governed by significant suppression of atomic displacement parameters correlated to the evolution of amplitude of atomic modulation functions. Abstract : Amongst the derivatives of 4‐biphenylcarboxylic acid and amino acid esters, the crystal structure of 4‐biphenylcarboxy‐(l )‐phenylalaninate is unusual owing to its monoclinic symmetry within a pseudo‐orthorhombic crystal system. The distortion is described by a disparate rotational property around the chiral centers (ϕchiral ≃ −129° and 58°) of the two molecules in the asymmetric unit. Each of these molecules comprises planar biphenyl moieties (ϕbiphenyl = 0°). Using temperature‐dependent single‐crystal X‐ray diffraction experiments we show that the compound undergoes a phase transition below T ∼ 124 K that is characterized by a commensurate modulation wavevector, q = δ(101), δ = ½. The (3+1)‐dimensional modulated structure at T = 100 K suggests that the phase transition drives the biphenyl moieties towards noncoplanar conformations with significant variation of internal torsion angle (ϕ max biphenyl ≤ 20°). These intramolecular rotations lead to dimerization of the molecular stacks that are described predominantly by distortions in intermolecular tilts (θmax ≤ 20°) and small variations in intermolecular distances (Δ d max ≃ 0.05 Å) between biphenyl molecules. Atypical of modulated structures and superstructures of biphenyl and other polyphenyls, the rotations of individual molecules are asymmetric (Δϕbiphenyl ≈ 5°) while ϕbiphenyl of one independent molecule is two to four times larger than the other. Crystal‐chemical analysis and phase relations in superspace suggest multiple competing factors involving intramolecular steric factors, intermolecular H—C…C—H contacts and weak C—H…O hydrogen bonds that govern the distinctively unequal torsional properties of the molecules.